Feasibility and acceptability of a hospital‐at‐home program for adolescents with eating disorders: Making progress in community/family‐based treatments. Issue 4 (18th March 2023) - Morón‐Nozaleda, Maria Goretti; Yáñez, Silvia; Camarneiro, Ricardo Antonio; Gutiérrez‐Priego, Silvia; Muñoz‐Domenjó, Andrea; García‐López, Cristina; Adrados García, Sandra; Jiménez García, Raquel; Trujillo, Eva Maria; Faya, Mar; Graell, Montserrat
Abstract: Objective: To explore the feasibility and acceptability of a novel hospital‐at‐home (HaH) program for adolescent patients with a severe eating disorder (ED). Method: Retrospective description of the program during its first year of activity. The feasibility construct is based on accessibility, recruitment, rate of retention, avoidance of hospital stays, and management of crisis situations. Caregivers completed a satisfaction questionnaire on discharge, including an item on perceived safety. All patients referred to the program were included. Results: Fifty‐nine female patients with a mean age of 14.69 years (SD = 1.67) were admitted. The mean stay was 39.14 days (SD = 14.47). On admission, 32.2% of patients presented nonsuicidal self‐harm behavior and 47.5% had comorbid mental disorders. All patients were screened in the first 48 h after referral, and the program retention rate was 91.52%. As for use of health services, 2016.03 hospital stays were avoided, and only 16.12% of the 31 calls received for urgent care required emergency department visits. Families gave the program an overall satisfaction score of 4.95/5, and all described it as "very safe." Discussion: The HaH program described is a feasible and acceptable care model in adolescents with severe EDs and comorbidities. Effectiveness studies should be performed. Public Significance: Eating disorders are a major concern for public health. The adolescent HaH program presented marks an advance in intensive community treatments for patients with severe EDs and comorbidities.